2016
DOI: 10.1186/s40064-016-2056-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some selected secondary metabolites and their invitro antioxidant activity in commercially available Ethiopian tea (Camellia sinensis)

Abstract: Eight brands of tea (Camellia sinensis),which are cultivated and commercially available in Ethiopian market, were analyzed for estimation of their total secondary metabolites (polyphenols, flavonoids and tannins) content and free radical scavenging activity which is expressed on dry weight basis. In this present study, the total polyphenols, tannin and flavonoid contents were studied spectrophotometrically using Folin–Dennis, Folin–Dennis/protein precipitation and aluminium chloride methods respectively. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
3
17
1
1
Order By: Relevance
“…Therefore, the actual content of TFC should be lower than that indicated by our data. However, using the same method used in our study, Lee et al (2016) and Bizuayehu et al (2016) determined the TFC in green tea and obtained highly similar results (2320 and 2340 mg catechin equivalent/100 g, respectively). Ot could be concluded that the total flavonoids in ATLs (mg/100 g) were similar to those in green tea and that ATLs were suitable for processing green tea for drinking.…”
Section: Total Flavonoid Content and Chlorogenic Acid Contentssupporting
confidence: 68%
“…Therefore, the actual content of TFC should be lower than that indicated by our data. However, using the same method used in our study, Lee et al (2016) and Bizuayehu et al (2016) determined the TFC in green tea and obtained highly similar results (2320 and 2340 mg catechin equivalent/100 g, respectively). Ot could be concluded that the total flavonoids in ATLs (mg/100 g) were similar to those in green tea and that ATLs were suitable for processing green tea for drinking.…”
Section: Total Flavonoid Content and Chlorogenic Acid Contentssupporting
confidence: 68%
“…adoensis were reported to possess analgesic activity ( Makonnen et al., 2003 ) and anti-pyretic activity ( Debell et al., 2005 ). The antioxidant properties in tandem with terpenoid contents of the essential oil of some of these spices have been reported by some researchers (e.g., Sishu et al., 2005 ; Eyob et al., 2008 ; Menghesa et al., 2011 ; Hailemariam and Shimelis, 2013 ; Bizuayehu et al., 2016 ; Debebe et al., 2018 ; Simur, 2018 ). However, antioxidant properties of these spices were not comparatively investigated from a standpoint of their phenolic contents.…”
Section: Introductionmentioning
confidence: 65%
“…The Folin–Dennis method [ 34 ] was used for the determination of total tannin content in extracts [ 36 ]. To 1 mL of extract, 2.5 mL of Folin–Dennis reagent (diluted with water 1:10) and 2 mL of Na 2 CO 3 solution (75 g/L) were added.…”
Section: Methodsmentioning
confidence: 99%